Minimum wage changes across provinces in China: Average treatment effects on employment and investment decisions - Ji Luo; Daniel J. Henderson (Journal of Risk and Financial Management, 2021)
We exploit data from the China Household Finance Survey to examine the impact of changes in the minimum wage on employment and investment decisions. We are able to non-parametrically identify the average treatment effect on the treated via exogenous variation in the minimum wage across provinces. We find that changes in the minimum wage had no adverse effects on employment (in terms of days worked per month or hours worked per work day) but found evidence that changes in the minimum wage impacted the percentage of families that had a bank account, a family in a rural area owned their home, and whether families (whose highest level of education was primary school) planned to purchase a home.
Keywords: 330; housing; minimum wage; non-parametric; treatment effects